2015
DOI: 10.3310/hta19290
|View full text |Cite
|
Sign up to set email alerts
|

Prasugrel (Efient®) with percutaneous coronary intervention for treating acute coronary syndromes (review of TA182): systematic review and economic analysis

Abstract: BackgroundAcute coronary syndromes (ACSs) are life-threatening conditions associated with acute myocardial ischaemia. There are three main types of ACS: ST segment elevation myocardial infarction (STEMI), non-ST segment elevation myocardial infarction (NSTEMI) and unstable angina (UA). One treatment for ACS is percutaneous coronary intervention (PCI) plus adjunctive treatment with antiplatelet drugs. Dual therapy antiplatelet treatment [aspirin plus either prasugrel (Efient®, Daiichi Sankyo Company Ltd UK/Eli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 88 publications
(206 reference statements)
0
9
0
Order By: Relevance
“…TRITON-TIMI 38 was also used to inform a cost-effectiveness modelling study for the UK in which 1-year health-care costs, excluding drug costs, were estimated to be £274 lower among patients with diabetes treated with prasugrel than among those with diabetes treated with clopidogrel. 101 The cost-effectiveness of treating ACS patients with DAPT with ticagrelor for 12 months instead of DAPT with clopidogrel in the Swedish setting was evaluated using data from the PLATO randomised trial. 135 This study found comparable total health-care costs, including the cost of study drugs, between the two treatment strategies (€96, 95% CI -€360 to €553 in 2010 Euros).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…TRITON-TIMI 38 was also used to inform a cost-effectiveness modelling study for the UK in which 1-year health-care costs, excluding drug costs, were estimated to be £274 lower among patients with diabetes treated with prasugrel than among those with diabetes treated with clopidogrel. 101 The cost-effectiveness of treating ACS patients with DAPT with ticagrelor for 12 months instead of DAPT with clopidogrel in the Swedish setting was evaluated using data from the PLATO randomised trial. 135 This study found comparable total health-care costs, including the cost of study drugs, between the two treatment strategies (€96, 95% CI -€360 to €553 in 2010 Euros).…”
Section: Discussionmentioning
confidence: 99%
“…The 12 eligible studies comprised two primary research studies 14,100 (Table 43) and 10 decision-analytic modelling studies [101][102][103][104][105][106][107][108][109][110] (Table 44). Utility decrements from the primary research studies, derived using differences in baseline and 6-month follow-up responses from the EQ-5D-3L, ranged from -0.0257 (95% CI -0.0365 to -0.0148) for minor bleeds to -0.0445 (95% CI -0.073 to -0.016) for major bleeds (see Table 43).…”
Section: Existing Utility Decrementsmentioning
confidence: 99%
See 3 more Smart Citations